The Effect Of Digital Organizational Culture on Organizational Performance With Business Digitalization and Digital Organizational Value as a Mediation In Elementary at Primary School In Batam City - Antony Sentoso; Putri Surya Sri Rahayu; Alden Nelson (Dinasti Publisher, 2024)
Technological developments have significantly changed the business landscape in recent decades. The digital revolution has been a critical driver of change in how organizations operate and interact with their customers. This study investigates the relationship between Organizational Performance with Digital Organizational Culture, Digital Business, and Digital Organizational Value. Innovations such as artificial intelligence, cloud computing, and data analytics have enabled organizations to improve operational efficiency, expand market reach, and create better customer experiences. However, success in adopting new technologies depends not only on infrastructure and systems but also on an organizational culture that supports innovation and change. This type of research is quantitative with a purposive sampling technique distributed through questionnaires to 242 respondents of private elementary school employees in Batam City. The results of data analysis were carried out using the Structural Equation Modeling (SEM) method. The results showed that Digital Organizational Culture, Business Digitalization, and Digital Organizational Value significantly affect Organizational Performance. By exploring these aspects, it is hoped that this research can provide valuable insights for organizational members and leaders in managing their digital transformation. Keywords: Organizational performance, Digital Organizational Culture, Business Digital, dan Digital Organizational Value, Technology.